The Effect of Guided Inquiry Learning Model and Scientific Performance on Student Learning Outcomes - Sri Mulyana; Rusdi Rusdi; Diana Vivanti (Indonesian Journal of Science and Education (IJOSE), 2018)
The purpose of research (1) Investigate the effect of guided Inquiry learning toward student learning result (2) Investigate the effect scientific performance to the student learning result (3) Investigate the interaction the guided Inquiry model and learning scientific performance toward the student learning result in sistem Excretion material. The research subjeck were 60 student of XI IPA 1 and 2 of SMAN 10 Pandeglang. Taken by simple random sampling. The data were analyzed by two tailed ANOVA test. Before the hypothesis was tested, normality and homogeneity test were done, the method that used in this research is quasi experiment with 2 x 2 factorial design. Based on the analyzed data, the highest score of the student learning result in experiment and control group were 90 and 85 with the means were 82 and 72. It can be concluded that: (1) there is significant influence of guided Inquiry learning the student learning result (2) there is significant influence of scientific performance to the student learning result (3) there is an interaction between guided Inquiry learning model and scientific performance toward the student learning result in Excretion system material. Based on the conclusions, it is suggested that the teacher’s ability is encouraged to dig deeper the student’s potential and performance. Keywords: learning outcome, Guided Inquiry, level of Scientific performance